A study on the therapeutic effect of zero-ray cardiac autonomic ganglion ablation on vasovagal syncope in a special occupational young population - Guo, Yan; Li, Si; Yang, Xiangyang; Hu, Jiaman; Liu, Jun; Gu, Xiaolong; Li, Yanzhuo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThis study aims to evaluate the safety and efficacy of zero-ray radiofrequency ablation of the cardiac autonomic ganglionic plexus (GP) for treating vasovagal syncope (VVS) in young individuals undergoing high-intensity physical training.MethodsWe retrospectively analyzed data from 35 young individuals with recurrent syncope (≥3 syncopal episodes within the year prior to the procedure) who underwent GP ablation at our hospital between May 2021 and January 2023. Among them, 33 (94.3%) were male, with a mean age of 22.7 ± 4.6 years. Systemic diseases and/or organic heart conditions that could cause syncope were excluded through comprehensive examinations upon admission. GP ablation was performed in patients with a positive upright tilt test. During the procedure, zero-ray septal puncture was guided by intracardiac ultrasound, and the GP was localized using the anatomical approach (AA) as the ablation target. The ablation endpoint was defined as an increase in heart rate to approximately 90 beats per minute. The safety and efficacy of the procedure were assessed by comparing preoperative and postoperative data, including heart rate, sinus node recovery time, atrioventricular (AV) Wenckebach point, heart rate variability (HRV), deceleration capacity of the heart (DC), and the occurrence of arrhythmias.ResultsNo intraoperative or postoperative complications were observed with zero-ray intracavitary ultrasound-guided GP ablation. Postoperatively, the sinus node recovery time and AV Wenckebach point were significantly shorter compared to preoperative values (P < 0.001). Both the postoperative mean ECG heart rate and the 12-month postoperative Holter mean heart rate were significantly higher than preoperative levels (P < 0.001). Additionally, sDANN-24, rMSSD, and deceleration capacity (DC) were significantly reduced postoperatively (P < 0.001). The follow-up period ranged from a minimum of 15 months to a maximum of 35 months. Within one year after surgery, two cases experienced a single episode of syncope, and one case reported a single episode of a syncopal premonitory aura. In the patient with a syncopal premonitory aura, outpatient ECG and Holter monitoring showed no abnormalities. The patient who experienced syncope was readmitted for further evaluation, including ECG, Holter monitoring, and an upright tilt test, which was negative. Two postoperative cases (one with a syncopal premonitory aura and one without syncope) exhibited second-degree type II AV block on Holter monitoring, which occurred during nocturnal sleep. Despite this, both groups were able to continue high-intensity physical training with significant symptomatic improvement.ConclusionsZero-ray cardiac GP ablation is a radiation-free, minimally invasive, safe, and effective treatment for young VVS patients undergoing high-intensity physical training.